The Effect of Nutrition Education on Nutritional Behaviors in Pregnant Women - ST Mirmolaei; M Moshrefi; A Kazemnejad; F Farivar; H Morteza (Tehran University of Medical Sciences, 2009)
Normal 0 false false false MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} Background & Objective: Prenatal period is a unique opportunity to assist the women to adopt healthy behaviors. The nutritional behaviors of pregnant women affect not only their own health but also the fetal growth and development. The purpose of this study was to determine the effect of nutrition education on nutritional behaviors in pregnant women."n"n Methods & Materials: In this randomized trial, 272 primigravida women were recruited using stratified cluster sampling method from eight family health clinics in Semnan. The participants were allocated in two groups randomly. The intervention group received the nutrition education through two 90-minute sessions with one week interval. Data were gathered using a questionnaire including demographic characteristics and nutritional behaviors at baseline and six weeks after the education. Data were analyzed in the SPSS."n"n Results: The results showed that there was not any significant difference in the mean score of the nutritional behaviors between two groups before the intervention. Significant difference was found between two groups after the intervention. The mean score in the intervention group was higher than in the control group (P<0.001)."n"n Conclusion: The results of the study showed that nutrition education affected the nutritional behaviors in pregnant women. Therefore, the nutrition education should be integrated in educational topics provided for pregnant women."n"n  "n"n Key words: prenatal care, nutrition, education, midwives